Isotopic evidence for human mobility in late antique Bulla Regia (Tunisia). (February 2023) - Nikita, Efthymia; Alexander, Michelle; Cox, Samantha; Radini, Anita; Le Roux, Petrus; Chaouali, Moheddine; Fenwick, Corisande
Highlights: First isotopic study on North African late antique mobility; Bulla Regia case study. 7 out of 22 late antique individuals nonlocal; 4 out of 5 comparative Romans local. Nonlocals could have originated in northern Tunisia, hence regional mobility. Inter-regional mobility from warmer areas possible for some individuals. First published values for bioavailable 87 Sr/ 86 Sr in northern Tunisia. Abstract: This paper represents the first isotopic study on late antique human mobility in North Africa, using the urban site of Bulla Regia in Tunisia as a case study. We also present the first values for bioavailable 87 Sr/ 86 Sr in northern Tunisia, analysing 63 plant and snail samples, as well as a simple method for the pre-processing of plants in the field to facilitate their export. Bulla Regia was a prominent Roman and late antique town situated on an important axis of transport and communication in North Africa and is therefore an ideal site to explore mobility in the region during this time period. Strontium ( 87 Sr/ 86 Sr) and oxygen (δ 18 OCarb ) isotopic analysis of 22 late antique individuals from a Christian church and cemetery identified at least seven or eight non-locals, while comparative analysis of five Roman individuals from a funerary enclosure on the same site classified all but one of them as potential locals. Most non-local individuals exhibit 87 Sr/ 86 Sr values that match various areas of northern Tunisia, which supports regional mobility rather than long-distance migration, although when combined with the oxygen results, inter-regional mobility from an area with a warmer climate may be hypothesised for some individuals. Examination of the spatial distribution of non-local individuals in their cemetery setting reveals that they were privileged individuals, thus they may reflect the mobility of wealthier town-dwellers in late antiquity, particularly perhaps along the Carthage-Hippo route.